A survived case of penetrating neck injury with intrathoracic organ damage - Atsushi Kagimoto; Takeshi Mimura; Nanami Hiraiwa; Yoshinori Yamashita (Surgical Case Reports, 2021)
Abstract Background Thoracic surgeons rarely encounter stab wounds with injury to the intrathoracic organs. However, such sudden and urgent situations could arise; therefore, experiences in managing such cases are invaluable. Case presentation An 84-year-old woman with depression who had a stab injury in the neck caused by a broad-bladed kitchen knife was brought to our facility by ambulance. She was stable in the emergency room; however, a computed tomography scan revealed that the blade had penetrated the right thoracic cavity. A right hemopneumothorax was seen. Considering the possibility of injury to the major vessels, a median sternotomy was performed. During the dissection around the blade, the patient started bleeding profusely, which required repair of an injury to the right internal jugular vein. The blade tip had penetrated the dorsal right upper lung lobe; however, it did not reach the hilum, and the knife was carefully removed. The damaged area of the lung was removed by wedge resection. Conclusion Patients with deep stab wounds from knives are often hemodynamically stable because the blade acts as tamponade and prevents hemorrhage. Therefore, a surgical approach that allows for good visualization should be considered for the extraction of the blade.